Basil (Ocimum Basilicum L.) as a Natural Antioxidant - Veronezi, Carolina Médici; Costa, Tainara; Jorge, Neuza (Wiley, 2012)
The antioxidant activity from basil ethanol extract, the effect on oxidative stability, total polar compounds, tocopherols levels and fatty acid profile in soybean oil under thermoxidation were evaluated. The basil leaves were dried in lyophilizer, ground and subjected to extraction with ethanol. The soybean oil (SO), soybean oil with 50mg/kg of tert-butylhydroquinone (TBHQ), soybean oil with 3,000mg/kg of extract (BE) and soybean oil with 3,000mg/kg of extract and 50mg/kg of TBHQ (mixture) treatments were subjected to 180±5C for 20h. Oil samples were taken at 0, 10 and 20h and subjected to analysis. The addition of the basil extract increased oxidative stability and resulted in lower formation of total polar compounds. Although the content of tocopherols and polyunsaturated fatty acids decreased over the course of heating, their values remained higher than the SO treatments. Synergistic effect was not observed in the mixture treatment. © 2012 Wiley Periodicals, Inc.